Regular Positive Human Contacts Do Not Improve Pigs’ Response to a Lipopolysaccharide Immune Challenge - Oceane Schmitt; Christian Knecht; Birgit Sobczak; Hana Volkmann; Ulrike Gimsa; Jean-Loup Rault (Neuroimmunomodulation)
Introduction: Little is known about the effects of a positive human-animal relationship on animal health and resilience. This study investigated the effects of regular positive human-animal interactions on pigs’ response to an immune challenge. Methods: Twenty-four female pigs were recruited at weaning (5 weeks old), and siblings of similar weights were allocated to either the positive contact treatment with positive contacts given by a human to groups of 3 pigs in their home pen or the control treatment only exposed to a human standing immobile and silently in front and outside their home pen. Treatment sessions were applied over 9 consecutive weeks, lasted 10 min per group, and occurred twice daily (morning and afternoon), 3 days a week. At 16 weeks of age, pigs were submitted to an immune challenge, which consisted of a single intravenous administration of lipopolysaccharide (LPS; 2 µg/kg). The sickness behaviours of pigs were observed using scan sampling every 5 min over 6 h post-administration, recording somnolence, vomiting, diarrhoea, cramping, shivering, and panting. Blood samples were taken before the LPS administration, after 1 h and 3 h. Blood plasma was analysed to quantify tumour necrosis factor alpha, interleukins 6 and 10, immunoglobulin A, and cortisol concentrations, and blood serum was analysed to quantify a brain-derived neurotrophic factor. Behavioural and physiological data were statistically analysed using general linear models in R. Results: Both treatments showed signs of sickness behaviour following LPS administration, but the two treatments did not differ in the frequency, severity of sickness behaviours, or length of recovery or in the blood plasma concentration of cytokines and cortisol measured. Conclusion: Therefore, regular exposure to positive contacts with a human over several weeks, although leading to the development of a positive human-animal relationship, did not enhance the pigs’ response to this immune challenge or the immune parameters measured in this study.